Development of a novel spherical stator multi-DOF ultrasonic motor using in-plane non-axisymmetric mode. (June 2020) - Huang, Zhibo; Shi, Shengjun; Chen, Weishan; Wang, Liang; Wu, Lijun; Liu, Yingxiang
Highlights: A multi-DOF ultrasonic motor using a piezoelectric spherical shell stator is proposed. This structure is beneficial to realize high symmetry and miniaturization. The proposed motor can rotate the rotor around X, Y and Z axes, respectively. A prototype is fabricated to verify the working principles, designs and simulations. The proposed motor has merits of compact size and high velocity. Abstract: A novel spherical stator multi-DOF ultrasonic motor using in-plane non-axisymmetric mode was proposed. The stator and the rotor of the motor adopt a piezoelectric ceramic spherical shell and two metal hemispherical shells, respectively, which is beneficial to realize high symmetry and miniaturization of the whole motor. The motor adopts the pair combination of three orthogonal in-plane non-axisymmetric modes to generate three types of elliptical motions at eight driving feet, which can rotate the rotor around X, Y and Z axes, respectively. Finite element method was used in the design of the proposed motor including searching for reasonable modes by modal analysis and verifying the uniform driving of the eight driving feet by transient analysis. A prototype was fabricated to verify the working principles, designs and simulations. The mechanical output characteristics around X, Y and Z axes were measured under different excitations, pre-tightening forces and loading conditions. The no-load rotary velocities of the prototype were 200 r/min, 198 r/min and 250 r/min and the maximum load torques were 10.8 mN·m, 11.0 mN·m and 12.3 mN·m around X, Y and Z axes, respectively. The spherical stator multi-DOF ultrasonic motor could be applied to robot visual driving systems as its merits of compact size and high velocity.